Expression patterns of anoctamin 1 and anoctamin 2 chloride channels in the mammalian nose - Dauner, Kristin; Lißmann, Judith; Jeridi, Semir; Frings, Stephan; Möhrlen, Frank (Cell & tissue research, 2012)
Calcium-activated chloride channels are expressed in chemosensory neurons of the nose and contribute to secretory processes and sensory signal transduction. These channels are thought to be members of